Application of aluminum-based MOF catalyst in catalytic synthesis of PET
By using aluminum-based MOF catalysts to form coordination bonds in PET synthesis, the problems of high toxicity and low activity of existing catalysts are solved, achieving environmentally friendly and efficient PET synthesis.
Patent Information
- Application Number
- CN202511364976.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-23
- Publication Date
- 2025-11-11
AI Technical Summary
Existing PET synthesis catalysts suffer from problems such as high toxicity, low activity, high cost, or scarcity of resources, making it difficult to achieve a balance between environmental protection and efficient catalysis.
Aluminum-based MOF catalysts are used, which utilize the large surface area and high porosity of the metal active sites in aluminum-based MOFs to form coordination bonds with carboxyl and hydroxyl groups, thereby reducing the activation energy of the reaction, catalyzing esterification and polycondensation reactions, and inhibiting the formation of side reactions.
It achieves environmentally friendly, efficient, and low-cost PET synthesis, with excellent product color value, high viscosity, and superior catalytic activity compared to traditional catalysts.
Smart Images

Figure CN120923758A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of material catalysis preparation technology, and in particular to the application of aluminum-based MOF catalysts in the catalytic synthesis of PET. Background Technology
[0002] PET (polyethylene terephthalate) is widely used in the fields of fiber, film, packaging materials and engineering plastics due to its excellent heat resistance, insulation, acid resistance and solvent resistance.
[0003] The synthesis of PET generally involves two steps: the first step is transesterification or esterification, and the second step is polycondensation. Both reactions require the presence of a catalyst, making catalysts crucial in the polyester production process. The following types of metal catalysts are used in the PET polyester industry:
[0004] ① Antimony-based catalysts: Among antimony-based catalysts, antimony trioxide, antimony acetate, and antimony glycolate are commonly used. When using antimony trioxide catalysts, the stabilizer phosphoric acid or phosphate ester is added. It is mainly used in the dimethyl terephthalate (DMT) process and the early terephthalic acid (PTA) process for polyester synthesis. However, antimony-based catalysts are often toxic. With increasing environmental awareness, there is a desire to reduce the amount of antimony used. This can be achieved by adding manganese, cobalt, zinc, etc., to antimony-based catalysts to prepare composite catalysts or by mixing them with other polyester catalysts, thus ensuring catalytic activity while reducing the amount of antimony used.
[0005] ② Titanium-based catalysts: In recent years, titanium-based catalysts have attracted much attention due to their high activity and greater environmental friendliness and economy compared to antimony-based catalysts. Currently, titanium-based catalysts include: titanium dioxide, tetraisopropyl titanate, tetrabutyl titanate, titanium glycolate, tetraphenyl titanate, and titanium acetylacetonate. The advantages of titanium-based catalysts are high activity, low price, and easy availability. The disadvantages are that titanate esters are prone to hydrolysis, affecting subsequent reactions, and the polyesters obtained using titanium-based catalysts have a slightly yellow color, thus limiting their use.
[0006] ③ Germanium-based catalysts: Commonly used catalysts include germanium dioxide and organometallic complexes of germanium. Moldform in the UK developed germanium dioxide powder in the 1990s, which was used to catalyze the synthesis of polyesters. Germanium dioxide exhibits good stability, mild reaction conditions, and few side reactions during the reaction. The added stabilizer phosphoric acid does not react with the catalyst, and the resulting polyester chips are pure white with high transparency. However, because germanium resources are scarce and expensive, and it easily volatilizes from the reaction system, this type of catalyst is suitable for preparing high-end polyester products.
[0007] ④ Tin-based catalysts: Commonly used catalysts include stannous oxalate, dibutyltin oxide, stannous octoate, and tin acetylacetonate. Other tin-based catalysts include stannous chloride, tin powder, tin oxide, and tin acetate. These catalysts exhibit good catalytic activity in the synthesis of polyesters, but the resulting polyesters have a less desirable color than those produced by antimony-based catalysts. Furthermore, tin is toxic, therefore these catalysts have not been used in industrial production.
[0008] Aluminum-based catalysts are characterized by their low cost and low toxicity. The catalytic activity of aluminum powder in polycondensation reactions has been reported, but its activity is lower compared to that of antimony and titanium compounds. Aluminum compound catalysts with catalytic activity in polycondensation reactions include aluminum phosphate, aluminum sulfate, aluminum nitrate, aluminum chloride, aluminum powder, clays (kaolin, mica, montmorillonite, burlite, sepiolite, etc.), 4A-molecular sieves, 5A-molecular sieves, aluminum phosphate molecular sieves, and alkyl aluminum (trimethylaluminum, triethylaluminum, tripropylaluminum, etc.), but their catalytic activity is generally low. Summary of the Invention
[0009] In view of this, the purpose of this invention is to provide the application of aluminum-based MOF catalysts in the catalytic synthesis of PET. The use of mild and stable aluminum-based MOF catalysts in the catalytic synthesis of PET can effectively reduce the activation energy of the reaction, accelerate the esterification and polycondensation reactions, and effectively suppress the formation of side reactions, thereby improving product quality.
[0010] The present invention solves the above-mentioned technical problems through the following technical means:
[0011] This application provides an application of an aluminum-based MOF catalyst in the catalytic synthesis of PET, the application including the following steps:
[0012] Terephthalic acid, ethylene glycol, and aluminum-based MOF are added to a reactor, and the air inside the reactor is replaced with nitrogen. The pressure inside the reactor is controlled at 200-300 kPa. The reactor is heated and stirred at 200-240°C for 2-8 hours. The pressure is then released to atmospheric pressure, and the temperature is raised to 260-300°C for negative compression polymerization for 1-4 hours. After pressurization and discharge, cooling, and pelletizing, PET is obtained.
[0013] In some embodiments, the mass ratio of terephthalic acid to ethylene glycol is 2:(1.0 to 2.0).
[0014] In some embodiments, the amount of aluminum-based MOF added is 0.01 to 0.05 wt% of terephthalic acid.
[0015] In some embodiments, the aluminum-based MOF is prepared as follows:
[0016] AlCl3·6H2O and terephthalic acid were dissolved and dispersed in water, DMF was added, and hydrofluoric acid was added while stirring at room temperature. After stirring for 20-60 min, the mixture was transferred to a reaction vessel lined with polytetrafluoroethylene and pressurized for reaction. The reaction solution was filtered, and the resulting solid product was washed and dried to obtain aluminum-based MOF.
[0017] In some embodiments, in the preparation method of the aluminum-based MOF, the mass ratio of aluminum chloride hexahydrate, terephthalic acid, water, DMF, and hydrofluoric acid is 12:(6-10):(180-200):(40-60):(3-8).
[0018] In some embodiments, the pressurization reaction is performed by heating for 8 to 16 hours at a pressure of 0.1 to 0.3 MPa and a temperature of 40 to 80°C.
[0019] This invention utilizes aluminum-based MOFs with large specific surface area and high porosity as catalysts for the PET polyester reaction. The aluminum in the MOF rapidly catalyzes the esterification reaction of terephthalic acid and ethylene glycol. The aluminum-based MOF acts on the carboxyl groups (-COOH) of terephthalic acid and the hydroxyl groups (-OH) of ethylene glycol, forming coordinate bonds with these groups through its surface metal active sites. This interaction lowers the activation energy of the reaction, thereby accelerating the esterification and polycondensation reactions. Simultaneously, aluminum-based MOFs are mild and stable catalysts; the coordinate bonds allow aluminum to gently catalyze the esterification reaction, suppressing side reactions and improving the product's color value. This invention provides a new solution for environmentally friendly, novel, and efficient PET polyester catalysts. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the synthesis process of the aluminum-based MOF catalyst of the present invention;
[0021] Figure 2 The XRD pattern of the aluminum-based MOF catalyst prepared in Example 1 is shown.
[0022] Figure 3 The image shows the TGA curve of the aluminum-based MOF catalyst prepared in Example 1. Detailed Implementation
[0023] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0024] In the embodiments of this application, the terms "exemplary" or "for example" are used to indicate that something is an example, illustration, or description. Any embodiment or design that is described as "exemplary" or "for example" in the embodiments of this application should not be construed as being more preferred or advantageous than other embodiments or designs. Specifically, the use of the terms "exemplary" or "for example" is intended to present the relevant concepts in a specific manner.
[0025] This invention provides a novel, environmentally friendly, efficient, inexpensive, and stable aluminum-based MOF catalyst for the catalytic synthesis of PET. This aluminum-based MOF catalyst exhibits higher catalytic activity than antimony and provides a milder catalytic reaction for polyester production, making it ideal for the efficient catalysis of PET polyester reactions. This aluminum-based MOF catalyst possesses the advantages of MOFs, such as large surface area and high porosity, while also containing aluminum metal active sites. The aluminum in the aluminum-based MOF can rapidly catalyze the esterification reaction of terephthalic acid and ethylene glycol. The aluminum-based MOF can act on the carboxyl groups (-COOH) of terephthalic acid and the hydroxyl groups (-OH) of ethylene glycol, forming coordinate bonds with the carboxyl and hydroxyl groups through its surface metal active sites. Through these interactions, the activation energy of the reaction is lowered, thereby accelerating the esterification and polycondensation reactions. Simultaneously, aluminum-based MOFs are a mild and stable catalyst; the coordinate bonds allow aluminum to gently catalyze the esterification reaction, suppressing side reactions and improving the product's color value. This application provides a new solution for environmentally friendly, novel, and efficient PET polyester catalysts.
[0026] Specifically, the application of the aluminum-based MOF catalyst in the catalytic synthesis of PET includes the following steps:
[0027] (1) Preparation of aluminum-based MOFs
[0028] Please refer to Figure 1 Aluminum chloride hexahydrate (AlCl3·6H2O) and terephthalic acid (H2BDC) were dissolved in water and ultrasonically dispersed until homogeneous. DMF was then added. Hydrofluoric acid was slowly added while stirring at room temperature. After stirring for 20–60 min, the mixture was transferred to a polytetrafluoroethylene-lined reactor, pressurized to 0.1–0.3 MPa, and heated to 40–80 °C for 8–16 h. After the reaction was complete, the mixture was filtered, and the resulting solid was washed repeatedly with water by centrifugation to remove the solvent. The resulting pale yellow solid was then dried in an oven for later use.
[0029] In this step, the mass ratio of aluminum chloride hexahydrate, terephthalic acid, water, DMF, and hydrofluoric acid is 12:(6-10):(180-200):(40-60):(3-8).
[0030] (2) Catalytic reaction of PET polyester
[0031] Terephthalic acid, ethylene glycol, and aluminum-based MOF are added to a reactor, and the air inside the reactor is replaced with nitrogen. The pressure inside the reactor is controlled at 200-300 kPa. The reactor is heated and stirred at 200-240°C for 2-8 hours. The pressure is then released to atmospheric pressure, and the temperature is raised to 260-300°C for negative compression polymerization for 1-4 hours. After pressurization and discharge, cooling, and pelletizing, PET is obtained.
[0032] In this step, the mass ratio of terephthalic acid to ethylene glycol is 2:(1.0 to 2.0), and the amount of aluminum-based MOF added is 0.01 to 0.05 wt% of terephthalic acid.
[0033] To better understand the above technical solutions, the following will provide a detailed explanation of the technical solutions in conjunction with the accompanying drawings and specific implementation methods.
[0034] Example 1
[0035] The application of the aluminum-based MOF catalyst in the catalytic synthesis of PET in this embodiment includes the following steps:
[0036] (1) Preparation of aluminum-based MOFs
[0037] 12g of aluminum chloride hexahydrate (AlCl3·6H2O) and 8.2g of terephthalic acid (H2BDC) were dissolved in 200g of water and ultrasonically dispersed until homogeneous. Then, 50g of DMF was added. 5g of hydrofluoric acid was slowly added while stirring at room temperature. After stirring for 30min, the mixture was transferred to a reaction vessel lined with polytetrafluoroethylene (PTFE), pressurized to 0.2MPa, heated to 60℃ and maintained for 14h. After the reaction was completed, the mixture was filtered, and the obtained solid was washed repeatedly with water by centrifugation to remove the solvent. The resulting pale yellow solid was then dried in an oven for later use, yielding aluminum-based MOF.
[0038] (2) Catalytic reaction of PET polyester
[0039] 2000g of terephthalic acid, 1200g of ethylene glycol, and 0.2g of aluminum-based MOF were added to a reactor. The air inside the reactor was replaced with nitrogen to control the pressure inside the reactor at 200kPa. The reactor was heated and stirred at 220℃ for 2 hours. The pressure was then released to atmospheric pressure, and the temperature was raised to 280℃ for negative compression polymerization for 2 hours. After being pressurized to atmospheric pressure, the material was discharged, cooled, and pelletized to obtain PET.
[0040] The XRD curve of the aluminum-based MOF catalyst prepared in this embodiment is shown in the figure. Figure 2 As shown, the TGA curves of the aluminum-based MOF catalyst are as follows: Figure 3 As shown. By Figure 1It can be seen that aluminum-based MOFs are rich in metal active sites. Through the metal active sites on their surface, they form coordination bonds with carboxyl and hydroxyl groups. By interacting with these groups, they reduce the activation energy of the reaction, thereby accelerating the PET polyester reaction. Figure 2 The image shows the XRD pattern of the aluminum-based MOF. The diffraction peaks of the experimental sample are consistent with the main peak type of the simulated model of the aluminum-based MOF, indicating that the aluminum-based MOF was successfully synthesized. Figure 3 This indicates that aluminum-based MOFs have good temperature resistance, reaching up to 434.2℃.
[0041] Example 2
[0042] The application of the aluminum-based MOF catalyst in the catalytic synthesis of PET in this embodiment includes the following steps:
[0043] (1) Preparation of aluminum-based MOFs
[0044] 12g of aluminum chloride hexahydrate (AlCl3·6H2O) and 8.2g of terephthalic acid (H2BDC) were dissolved in 200g of water and ultrasonically dispersed until homogeneous. Then, 50g of DMF was added. 5g of hydrofluoric acid was slowly added while stirring at room temperature. After stirring for 30min, the mixture was transferred to a reaction vessel lined with polytetrafluoroethylene (PTFE), pressurized to 0.2MPa, heated to 60℃ and maintained for 14h. After the reaction was completed, the mixture was filtered, and the obtained solid was washed repeatedly with water by centrifugation to remove the solvent. The resulting pale yellow solid was then dried in an oven for later use, yielding aluminum-based MOF.
[0045] (2) Catalytic reaction of PET polyester
[0046] 2000g of terephthalic acid, 1200g of ethylene glycol, and 0.6g of aluminum-based MOF were added to a reactor. The air inside the reactor was replaced with nitrogen to control the pressure inside the reactor at 200kPa. The reactor was heated and stirred at 220℃ for 2 hours. The pressure was then released to atmospheric pressure, and the temperature was raised to 280℃ for negative compression polymerization for 2 hours. After being pressurized to atmospheric pressure, the material was discharged, cooled, and pelletized to obtain PET.
[0047] Example 3
[0048] The application of the aluminum-based MOF catalyst in the catalytic synthesis of PET in this embodiment includes the following steps:
[0049] (1) Preparation of aluminum-based MOFs
[0050] 12g of aluminum chloride hexahydrate (AlCl3·6H2O) and 8.2g of terephthalic acid (H2BDC) were dissolved in 200g of water and ultrasonically dispersed until homogeneous. Then, 50g of DMF was added. 5g of hydrofluoric acid was slowly added while stirring at room temperature. After stirring for 30min, the mixture was transferred to a reaction vessel lined with polytetrafluoroethylene (PTFE), pressurized to 0.2MPa, heated to 60℃ and maintained for 14h. After the reaction was completed, the mixture was filtered, and the obtained solid was washed repeatedly with water by centrifugation to remove the solvent. The resulting pale yellow solid was then dried in an oven for later use, yielding aluminum-based MOF.
[0051] (2) Catalytic reaction of PET polyester
[0052] 2000g of terephthalic acid, 1200g of ethylene glycol, and 1g of aluminum-based MOF were added to a reactor. The air inside the reactor was replaced with nitrogen to control the pressure inside the reactor at 200kPa. The reactor was heated and stirred at 220℃ for 2 hours. The pressure was then released to atmospheric pressure, and the temperature was raised to 280℃ for negative compression polymerization for 2 hours. After being pressurized to atmospheric pressure, the material was discharged, cooled, and pelletized to obtain PET.
[0053] Example 4
[0054] The application of the aluminum-based MOF catalyst in the catalytic synthesis of PET in this embodiment includes the following steps:
[0055] (1) Preparation of aluminum-based MOFs
[0056] 12g of aluminum chloride hexahydrate (AlCl3·6H2O) and 6g of terephthalic acid (H2BDC) were dissolved in 180g of water and ultrasonically dispersed until homogeneous. Then, 40g of DMF was added. 3g of hydrofluoric acid was slowly added while stirring at room temperature. After stirring for 20 minutes, the mixture was transferred to a reaction vessel lined with polytetrafluoroethylene (PTFE), pressurized to 0.1MPa, and heated to 40℃ for 16 hours. After the reaction was completed, the mixture was filtered, and the obtained solid was washed repeatedly with water by centrifugation to remove the solvent. The resulting pale yellow solid was then dried in an oven for later use, yielding aluminum-based MOF.
[0057] (2) Catalytic reaction of PET polyester
[0058] 2000g of terephthalic acid, 1000g of ethylene glycol, and 0.8g of aluminum-based MOF were added to a reactor. The air inside the reactor was replaced with nitrogen to control the pressure inside the reactor at 220kPa. The reactor was heated and stirred at 200℃ for 5 hours. The pressure was then released to atmospheric pressure, and the temperature was raised to 260℃ for negative compression polymerization for 1 hour. After being pressurized to atmospheric pressure, the material was discharged, cooled, and pelletized to obtain PET.
[0059] Example 5
[0060] The application of the aluminum-based MOF catalyst in the catalytic synthesis of PET in this embodiment includes the following steps:
[0061] (1) Preparation of aluminum-based MOFs
[0062] 12g of aluminum chloride hexahydrate (AlCl3·6H2O) and 10g of terephthalic acid (H2BDC) were dissolved in 190g of water and ultrasonically dispersed until homogeneous. Then, 60g of DMF was added. 8g of hydrofluoric acid was slowly added while stirring at room temperature. After stirring for 60min, the mixture was transferred to a reaction vessel lined with polytetrafluoroethylene (PTFE), pressurized to 0.3MPa, heated to 80℃ and maintained for 8h. After the reaction was complete, the mixture was filtered, and the resulting solid was washed repeatedly with water by centrifugation to remove the solvent. The resulting pale yellow solid was then dried in an oven for later use, yielding aluminum-based MOF.
[0063] (2) Catalytic reaction of PET polyester
[0064] 2000g of terephthalic acid, 2000g of ethylene glycol, and 0.8g of aluminum-based MOF were added to a reactor. The air inside the reactor was replaced with nitrogen to control the pressure inside the reactor at 300kPa. The reactor was heated and stirred at 240℃ for 8 hours. The pressure was then released to atmospheric pressure, and the temperature was raised to 300℃ for negative compression polymerization for 4 hours. After being pressurized to atmospheric pressure, the material was discharged, cooled, and pelletized to obtain PET.
[0065] Comparative Example 1
[0066] The preparation method of PET in this comparative example is as follows:
[0067] 2000g of terephthalic acid and 1200g of ethylene glycol were added to a reactor. The air inside the reactor was replaced with nitrogen to control the pressure inside the reactor at 200kPa. The reactor was heated and stirred at 220℃ for 2 hours. The pressure was then released to atmospheric pressure and the temperature was raised to 280℃ for negative compression polymerization for 2 hours. After being pressurized to atmospheric pressure, the material was discharged, cooled, and pelletized to obtain PET.
[0068] Comparative Example 2
[0069] The preparation method of PET in this comparative example is as follows:
[0070] 2000g of terephthalic acid, 1200g of ethylene glycol, and 0.6g of antimony trioxide were added to a reactor. The air inside the reactor was replaced with nitrogen to control the pressure inside the reactor at 200kPa. The reactor was heated and stirred at 220℃ for 2 hours. The pressure was then released to atmospheric pressure, and the temperature was raised to 280℃ for negative compression polymerization for 2 hours. After being pressurized to atmospheric pressure, the material was discharged, cooled, and pelletized to obtain PET.
[0071] The PET samples prepared in Examples 1-3 and Comparative Examples 1-2 were used as test samples. The color of the samples was tested using a Data Color 500 colorimeter, and the viscosity of the samples was tested using a BP160 automatic Ubbelohde viscometer. The test results are shown in Table 1.
[0072]
[0073] Table 1
[0074] In Table 1, L represents brightness, and 0-100 represents the range from black to white, i.e., the lightness or darkness of the color; a represents the red-green color of the sample, with positive values indicating red and negative values indicating green; b represents the yellow-blue color of the object, with positive values indicating yellow and negative values indicating blue.
[0075] Table 1 shows that the PET prepared in Examples 1-3 has high brightness and low b-value. The PET prepared with 0.03 wt% aluminum-based MOF (Example 2) achieved a brightness of up to 80.0 and a b-value of up to 3.0, with a viscosity of 0.82 dL / g. Comparative Example 1, without aluminum-based MOF, yielded a sample with a viscosity of only 0.23 dL / g after the reaction, making it difficult to mold, indicating a lower degree of polymerization in the PET without aluminum-based MOF. Comparative Example 2, using the same proportion of antimony trioxide, produced PET flakes with lower brightness, higher b-value, a yellowish color, and a viscosity of only 0.52 dL / g. The addition of 0.03 wt% aluminum-based MOF as a catalyst resulted in the best polyester performance for the PET.
[0076] The aluminum-based MOF synthesis method of this invention is simple, requiring no high temperature or harsh reaction conditions; the reaction can be completed at 60°C. Furthermore, in the catalytic polyester reaction of PET, the amount of aluminum-based MOF added is small; only 0.03 wt% is needed to achieve excellent color value and viscosity in the prepared PET.
[0077] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the present invention, and all such modifications and substitutions should be covered within the scope of the claims of the present invention. Technical aspects, shapes, and structures not described in detail in this invention are all well-known technologies.
Claims
1. The application of aluminum-based MOF catalysts in the catalytic synthesis of PET, characterized in that, The application includes the following steps: Terephthalic acid, ethylene glycol, and aluminum-based MOF are added to a reactor, and the air inside the reactor is replaced with nitrogen. The pressure inside the reactor is controlled at 200-300 kPa. The reactor is heated and stirred at 200-240°C for 2-8 hours. The pressure is then released to atmospheric pressure, and the temperature is raised to 260-300°C for negative compression polymerization for 1-4 hours. After pressurization and discharge, cooling, and pelletizing, PET is obtained.
2. The application of the aluminum-based MOF catalyst according to claim 1 in the catalytic synthesis of PET, characterized in that, The mass ratio of terephthalic acid to ethylene glycol is 2:(1.0 to 2.0).
3. The application of the aluminum-based MOF catalyst according to claim 2 in the catalytic synthesis of PET, characterized in that, The amount of aluminum-based MOF added is 0.01 to 0.05 wt% of terephthalic acid.
4. The application of the aluminum-based MOF catalyst according to claim 1 in the catalytic synthesis of PET, characterized in that, The preparation method of the aluminum-based MOF is as follows: AlCl3·6H2O and terephthalic acid were dissolved and dispersed in water, DMF was added, and hydrofluoric acid was added while stirring at room temperature. After stirring for 20-60 min, the mixture was transferred to a reaction vessel lined with polytetrafluoroethylene and pressurized for reaction. The reaction solution was filtered, and the resulting solid product was washed and dried to obtain aluminum-based MOF.
5. The application of the aluminum-based MOF catalyst according to claim 4 in the catalytic synthesis of PET, characterized in that, In the preparation method of the aluminum-based MOF, the mass ratio of aluminum chloride hexahydrate, terephthalic acid, water, DMF and hydrofluoric acid is 12:(6-10):(180-200):(40-60):(3-8).
6. The application of the aluminum-based MOF catalyst according to claim 4 in the catalytic synthesis of PET, characterized in that, The pressurized reaction is carried out by heating for 8 to 16 hours at a pressure of 0.1 to 0.3 MPa and a temperature of 40 to 80°C.